Comments on the article “Monitoring COVID-19 is like instrument flying” - Pokrajac, David D. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Comments on the article “Monitoring COVID-19 is like instrument flying”
Keywords: comments; COVID-19; Gaussian curve; S-curve